Problem-based learning in dentistry, implementation, and student perceptions - Jayashri Tamanna Nerali; Lahari Ajay Telang; Ajay Telang; Pishipati Vinayak Kalyan Chakravarthy (Wolters Kluwer Medknow Publications, 2020)
Introduction: Problem-based learning (PBL) is one of the most comprehensive and widely accepted student-centered tool for teaching and learning health professions education, wherein students define the problem, establish learning objectives, undergo self-directed learning and facilitate understanding of the problems. This study has been carried out with an aim of assessing 3rd year dental student's perception of PBL as a teaching and learning method over a 5-year period based on problem-solving and self-directed learning, cooperative learning, role of facilitator and product discussion. Methodology: The perception of 3rd year students from year 2014 to 2018 was assessed at the end of PBL sessions using a self-administered, structured questionnaire. Their responses were recorded using a five point Likert scale and data collected retrospectively was analyzed. Students' open feedback regarding the PBL process was also recorded and analyzed. Results: A total of 376 participants responded to the questionnaire (female = 250 [65%], male = 126 [35%]). Majority of students agreed that PBL improved problem-solving skill, self-directed learning and perceived that it had a positive impact on cooperative learning. Students also felt that PBL product discussion prepared them for future presentation and helped to clarify concepts. Conclusion: The results suggested that students had a positive attitude toward PBL and it improved their problem-solving skills as well as motivated them to learn and participate actively. Some students felt that PBL was time consuming, yet it was a fun and interesting way to learn.